Expression and functional role of α7 nicotinic receptor in human cytokine-stimulated natural killer (NK) cells - Zanetti, Samanta Romina (2016)
The homomeric α7 nicotinic receptor (nAChR) is one of the most abundant nAChRs in the central nervous system where it contributes to cognition, attention, and working memory. α7 nAChR is also present in lymphocytes, dendritic cells (DCs), and macrophages and it is emerging as an important drug target for intervention in inflammation and sepsis. Natural killer (NK) cells display cytotoxic activity against susceptible target cells and modulate innate and adaptive immune responses through their interaction with DCs. We here show that human NK cells also express α7 nAChR. α7 nAChR mRNA is detected by RT-PCR and cell surface expression of α7 nAChR is detected by confocal microscopy and flow cytometry using α-bungarotoxin, a specific antagonist. Both mRNA and protein levels increase during NK stimulation with cytokines (IL-12, IL-18, and IL-15). Exposure of cytokine-stimulated NK cells to PNU-282987, a specific α7 nAChR agonist, increases intracellular calcium concentration ([Ca(2+)]i) mainly released from intracellular stores, indicating that α7 nAChR is functional. Moreover, its activation by PNU-282987 plus a specific positive allosteric modulator greatly enhances the Ca(2+) responses in NK cells. Stimulation of NK cells with cytokines and PNU-282987 decreases NF-κB levels and nuclear mobilization, down-regulates NKG2D receptors, and decreases NKG2D-dependent cell-mediated cytotoxicity and IFN-γ production. Also, such NK cells are less efficient to trigger DC maturation. Thus, our results demonstrate the anti-inflammatory role of α7 nAChR in NK cells and suggest that modulation of its activity in these cells may constitute a novel target for regulation of the immune response.